Socratic dialogue in logotherapy - Salomón Paredes, Alejandro Khaled (2014)
In this article a detailed application framework called Socratic Dialogue as the main psychotherapeutic tool of Logotherapy, delving into the methodology, the attitude of the therapist and the fields of intervention is made about the person. Numerous examples of approaches, key questions and remarks are included. It goes to authors such as V. Frankl, E. Lukas, J. Fabry, E. Martinez, among others, in relation to which this form of therapeutic conversation is in order to mobilize the freedom of each client.